MODERN TECHNOLOGIES OF RESOURCE MANAGEMENT OF INDUSTRIAL ENTERPRISES ON THE BASIS OF LEAN PRODUCTION - HAVLOVSKA, Nataliia; KRYVDYK, Mykhailo; RUDNICHENKO, Yevhenii; ZATSERKOVNY, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the main provisions of resource management optimization due to the implementation of lean production, in particular, the main types of costs are presented (overproduction, loss of time due to waiting, excess transportation, excess processing, excess stocks, excess movements, defects, unrealized creative potential of employees), definition of the concept "lean production" and classical principles of lean production are given. The definition of lean production is given, namely, it is a philosophy that involves avoiding or eliminating existing losses, due to the use of lean production tools, in order to achieve the maximum efficiency of the enterprise. A study of the main tools of lean manufacturing was carried out by analyzing the "Toyota Production System (TPS) house", which is based on the principles of better value, quality, delivery, empowerment, customer-focused culture. The tools of "lean production" are characterized, in particular Standard work - standardized work, Heijunka - ensuring the possibility of uniform deliveries of various types of products, Averaged daily volume and mix - "smoothing", standardization of fluctuations in the order cycle, Smooth production schedule - "smooth" production schedule, Kaizen - continuous improvement of activities, Just in time - "exactly on time", Takt time - clock frequency of order fulfillment, One piece flow - flow of single products, Downstream - "pulling" from below, Jidora - automation, Built in quality - built-in quality, Poka-yoke - error protection, 5 Whys, Harmony of man and machine - rational loading of machines by multi-functional workers, 5S - sorting, maintaining order, keeping clean, standardization, improvement, Visual control - coverage, "at a glance", transparency technical process, Kanban – inventory and production management, SMED – rapid reconfiguration of equipment, TPM – with general equipment maintenance system, 3P (production preparation process) – production preparation process, Creative ideas suggestion system – system of collecting the best ideas.